Porous silicon nitride ceramic and preparation method thereof
By embedding pure silicon nitride blanks into powder doped with sintering aids and sintering, the problem of performance degradation caused by uneven distribution of sintering aids is solved, and high-performance, low-cost porous silicon nitride ceramics are achieved.
Patent Information
- Application Number
- CN202411516547.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
AI Technical Summary
During the sintering process, the existing porous silicon nitride ceramics have large differences in grain size and reduced performance. The presence of the internal liquid phase leads to shrinkage and residual miscellaneous phases.
Using a method that does not require the addition of sintering aids to the silicon nitride blank, the pure silicon nitride blank is buried in powder doped with sintering aids for sintering, and the diffusion reaction of external sintering aids is used to promote the transformation of α-Si3N4 into β-Si3N4, thereby reducing sintering aid residue and improving material performance.
A porous silicon nitride ceramic with no grain boundary impurities and well-developed grains has been achieved. The product has small shrinkage, excellent performance and low cost.
Smart Images

Figure CN119330723A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a porous silicon nitride ceramic and a preparation method thereof. Background Art
[0002] Space astronomical telescopes need to use a large array of spliced CCD detector focal planes during sky surveys, and the equipment will generate a lot of heat during observations. To ensure the normal operation of the equipment, high-power loop heat pipes are the most effective means of thermal management for spacecraft. Among them, the capillary pump main core, as one of the most critical components in the loop heat pipe, is the key to the stable operation of the spacecraft at a constant temperature. Compared with metal capillary pumps, ceramic capillary pumps have the advantages of light weight, stability, high strength and corrosion resistance, and can control temperature more accurately, improve the thermal balance of space cameras, and improve imaging quality. Porous silicon nitride (Si3N4) ceramics have good mechanical strength and rigidity, and the shape and size of the pores of the porous body do not change under air pressure, hydraulic pressure or other stress loads. It has been used to prepare the capillary pump main core of the loop heat pipe.
[0003] Chinese patent CN111196729B provides a method for preparing porous silicon nitride ceramics with ultra-low sintering aid content, by burying powder sintering a blank composed of silicon powder, silicon nitride powder and sintering aid to make porous silicon nitride ceramics to prepare porous silicon nitride ceramics; Chinese patents CN103121854B and CN102320856B both prepare high-strength porous silicon nitride ceramics by burying powder sintering a silicon nitride blank containing sintering aids; in including but not limited to the above patents, the sintering aid inside the blank may be unevenly mixed, resulting in excessive local liquid phase, which in turn causes large differences in grain size and even affects the overall performance of the material; in addition, the presence of the internal liquid phase makes it inevitable that the grains will shrink during the rearrangement process, and even residual impurities will remain, resulting in performance degradation. Summary of the invention
[0004] The purpose of the present invention is to provide a porous silicon nitride ceramic and a preparation method thereof in order to overcome at least one of the defects of the above-mentioned prior art. Compared with the prior art, the present invention does not need to add a sintering aid to the silicon nitride blank. By burying the pure silicon nitride blank in a powder doped with a sintering aid and sintering it, a porous silicon nitride ceramic with no grain boundary impurities and perfect grain development can be obtained, and a silicon nitride ceramic with the advantages of low cost, small product shrinkage and excellent performance can be obtained.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the purposes of the present invention is to provide a porous silicon nitride ceramic, wherein the silicon nitride ceramic is formed by overlapping long rod-shaped grains, and the long rod-shaped grains are composed of β-Si3N4;
[0007] The total porosity of the silicon nitride ceramic is 30% to 70%, the bending strength is 40 to 600 MPa, and the linear shrinkage is 0.2% to 1%.
[0008] Furthermore, the length of the grains in the silicon nitride ceramic is 0.2-10 μm, the diameter is 0.1-2 μm, and the average aspect ratio is 5-15.
[0009] A second object of the present invention is to provide a method for preparing the porous silicon nitride ceramic as described above, comprising the following steps:
[0010] S1, gel injection molding silicon nitride ceramic green body;
[0011] S2, mixing silicon powder, silicon nitride powder, sintering aid and boron nitride powder to obtain a buried powder raw material;
[0012] S3, removing organic matter from the ceramic green body, and embedding the obtained green body with embedding powder raw materials, and obtaining porous silicon nitride ceramics after sintering.
[0013] Furthermore, the preparation method of the silicon nitride ceramic green body is as follows:
[0014] S11, uniformly mixing the monomer, cross-linking agent, polymerization inhibitor, pH agent, dispersant and water to obtain a polymer premix solution;
[0015] S12, selecting silicon nitride powder as the ceramic powder;
[0016] S13, mixing the polymer premix and the ceramic powder evenly, and dispersing them by ball milling to obtain a ceramic slurry;
[0017] S14, adding an initiator and a catalyst to the ceramic slurry, pouring it into a mold for molding, and obtaining a silicon nitride ceramic green body.
[0018] Further, in S12, the silicon nitride powder satisfies at least one of the following conditions:
[0019] ① The silicon nitride powder is composed of α-type silicon nitride powder and β-type silicon nitride powder, and the ratio of the two is (0-100):(100-0);
[0020] ② The median particle size of the silicon nitride powder is 0.5 to 10 μm.
[0021] Furthermore, in S13, the solid phase volume content of the ceramic slurry is 15% to 65%, and the high molecular polymer content is 1% to 10% of the total mass of the ceramic slurry.
[0022] Furthermore, in S2, the mixed powder is prepared specifically as follows: silicon powder, silicon nitride powder, sintering aid and boron nitride powder are poured into a ball mill, wet-mixed for at least 48 hours using alcohol as a ball milling medium to obtain a slurry with uniform components, the slurry is placed in a constant temperature oven at a maximum of 90° C. and dried for at least 12 hours, and sieved to obtain a mixed powder.
[0023] Furthermore, in S2, the sintering aid powder is one or more of yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide, neodymium oxide, lutetium oxide and magnesium silicon nitride.
[0024] Furthermore, in S2, the mass ratio of silicon nitride powder, sintering aid powder and boron nitride powder in the powder embedding raw material is (0.1-0.5):(0.5-0.1):(0.4).
[0025] Furthermore, in S3, the organic matter in the porous silicon nitride ceramic precursor is removed specifically by: heating to 400-800°C in an air environment, keeping warm for 2-6 hours, and eliminating the organic matter in the ceramic blank; pouring the buried powder raw material into the sintering crucible, occupying 50%-70% of the volume of the crucible, and then burying the ceramic blank into the powder in the crucible; sintering is gas pressure sintering, and the sintering temperature is 1600-1700°C, wherein the heating rate of 400-800°C is 0.5-2°C / min, the heating rate of 800-1200°C is 3-6°C / min, the heating rate of 1200-1700°C is 5-10°C / min, and the holding time is 1-2h.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] (1) The porous silicon nitride ceramic of the present invention has no grain boundary impurities and has well-developed grains, and has the advantages of small product shrinkage and excellent performance.
[0028] (2) The present invention does not require the addition of sintering aids to the blank. By burying pure silicon nitride in powder containing sintering aids for sintering, there is a difference in the concentration of sintering aids inside and outside the blank. When sintering the pure silicon nitride blank, the external sintering aid will diffuse into the blank and react with the surface silicon dioxide to form a liquid phase, promoting the transformation of α-Si3N4 into β-Si3N4. After α-Si3N4 is completely transformed into β-Si3N4, the sintering aid will no longer diffuse into the blank. In the present invention, the external sintering aid can "adapt" to the phase change reaction inside the blank, greatly reducing the excess sintering aid remaining inside the blank and improving the performance of the blank.
[0029] (3) The powder embedding method used in the present invention can use the powder embedding raw materials multiple times, which can greatly reduce the cost. High-performance porous silicon nitride ceramics can be obtained by using this method. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart of preparing porous silicon nitride ceramics in Example 1 of the present invention.
[0031] Figure 2 1 is an XRD picture of the porous silicon nitride ceramic prepared in the embodiment of the present invention.
[0032] Figure 3 is a SEM photograph of the SN-A type porous silicon nitride ceramic prepared in the embodiment of the present invention.
[0033] Figure 4 is a SEM photograph of the SN-B type porous silicon nitride ceramic prepared in the embodiment of the present invention.
[0034] Figure 5 3 is a SEM photograph of the SN-C type porous silicon nitride ceramic prepared in the embodiment of the present invention. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0036] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the endpoints of the range is included in the range. Thus, each point or single value can be combined as its own lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unambiguous range.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0038] As one of the most critical components in the loop heat pipe, the high-performance porous silicon nitride ceramic capillary pump core is the key to the stable operation of spacecraft at a constant temperature. Existing technologies often prepare silicon nitride blanks by adding sintering aids, which face challenges such as uniform powder dispersion and uniform grain growth in the mixing and sintering stages. However, research has found that direct sintering of pure silicon nitride using buried powder has the advantages of uniform grain growth, low cost and excellent performance, which is a new method that can overcome the above problems.
[0039] Based on this, the present invention proposes the following technical solutions.
[0040] A first aspect of an embodiment of the present invention provides a method for preparing a porous silicon nitride ceramic, comprising the following steps:
[0041] S1, Gel injection molding: molding silicon nitride ceramic blanks with different solid content or gel content; gel injection molding technology can form ceramic blanks with complex shapes in net size, reduce the cost of subsequent ceramic processing, and reduce or eliminate defects such as agglomeration of ceramic particles, macroscopic pores, cracks, etc. in the material, thereby improving the reliability of the material. For ceramics that have been illegally processed or modified, this technology can be used for mechanical pre-processing at the blank stage.
[0042] In some embodiments of the present invention, in step S1, the specific method for preparing the silicon nitride ceramic blank is:
[0043] S11, preparing a polymer premix: mixing monomers, a cross-linking agent, a defoaming agent, a pH agent, a dispersant, and water;
[0044] S12, preparing ceramic powder: silicon nitride powder;
[0045] In some embodiments of the present invention, the mass fraction of silicon nitride powder is: 100%, wherein the silicon nitride powder is divided into α-Si3N4 powder and β-Si3N4 powder, and their mass ratio is: α-type silicon nitride powder: β-type silicon nitride powder = x: (100~x), (x is 0~100).
[0046] Preferably, the mass ratio of α-type silicon nitride powder to β-type silicon nitride powder is 80:20.
[0047] In some embodiments of the present invention, the median particle size of the silicon nitride powder is 0.5 to 10 μm. For example, the median particle size of the silicon nitride powder can be 0.5 μm, 1 μm, 1.5 μm, 5 μm, 10 μm or any value within the above range, preferably 0.5 μm. The smaller the particle size of the powder, the better the sintering activity.
[0048] In addition, when determining silicon nitride ceramic blanks with different solid contents, the solid content and water content in the silicon nitride ceramic blank are first determined. For example, when determining the solid content, the mass of each substance / the specific gravity of each substance / (the mass of each substance / the specific gravity of each substance+the mass of water) is the solid content. After the mass of water is confirmed, the masses of the remaining additives can also be confirmed.
[0049] S13, preparing ceramic slurry: mixing polymer premixed liquid and ceramic powder, and dispersing by ball milling to obtain ceramic slurry;
[0050] Specifically, after mixing, the mixture is placed in a silicon nitride tank for ball milling, stirring and dispersing, with a ball milling speed of 200 to 400 r / min and a time of 2 to 24 hours;
[0051] Preferably, the ball milling speed is 300-350 r / min, and the time is 8-24 h;
[0052] Preferably, the ball milling speed is 300 r / min and the time is 12 h.
[0053] In some embodiments of the present invention, the solid content of the ceramic slurry is 25% to 65%. Specifically, when the solid content in the slurry is too high, the fluidity is poor, and when the solid content is too low, it cannot be formed. The ceramic slurry includes the following components by mass fraction: 35% to 75% deionized water (for example, the mass fraction of deionized water can be 35%, 45%, 55%, 65%, 75% or any value within the above range), 1% to 10% monomer (for example, the mass fraction of the monomer can be 1%, 2%, 5%, 10% or any value within the above range), 0.1% to 1% cross-linking agent (for example, the mass of the cross-linking agent can be 0.1%, 0.2%, 0.5%, 1.0% or any value within the above range), 0.08% to 0.23% inhibitor (for example, the mass fraction of the inhibitor can be 0.08%, 0.1 %, 0.12%, 0.15%, 0.20%, 0.23% or any value within the above range), 0.05% to 0.2% dispersant (for example, the mass fraction of the dispersant can be 0.05%, 0.08%, 0.10%, 0.15%, 0.20% or any value within the above range), 0.1% to 0.3% pH agent (for example, the mass fraction of the pH agent can be 0.1%, 0.2%, 0.3% or any value within the above range), and the balance is ceramic powder. Of course, those skilled in the art should understand that the above range values can be arbitrarily combined but the sum must be equal to 100%, and no further examples are given here.
[0054] In some embodiments, the monomer is acrylamide;
[0055] The cross-linking agent is N,N'-methylenebisacrylamide, which is used to transform linear or slightly branched macromolecules into a three-dimensional network structure, thereby improving the strength, heat resistance, wear resistance, solvent resistance and other properties;
[0056] The polymerization inhibitor is catechol or phenothiazine, preferably catechol, and the function of the polymerization inhibitor is to prevent the gel reaction from occurring too quickly and ensure that the slurry will not solidify when vacuuming;
[0057] The pH agent is ammonia water or acetic acid. The function of the pH agent is to adsorb a layer of electrons on the surface of the powder material, so that the particles do not agglomerate together through electrostatic repulsion.
[0058] The dispersant is one of triethylhexyl phosphate, sodium dodecyl sulfate, ammonium polyacrylate and tetramethylammonium hydroxide, preferably ammonium polyacrylate (PAA-NH4), which mainly functions to disperse the powder in water so that it does not agglomerate together. Its dispersibility is higher than that of general water-resistant dispersants, so its usage is less and it can be industrialized on a large scale.
[0059] S14, polymerization: adding an initiator and a catalyst to the ceramic slurry to react;
[0060] Specifically, initiators and catalysts can initiate and promote the polymerization of monomers.
[0061] In some embodiments, the initiator is one of a hydrogen peroxide solution, an ammonium persulfate solution, and a benzoyl peroxide solution, preferably an ammonium persulfate solution, and the catalyst is tetramethylethylenediamine.
[0062] In some embodiments, the added initiator and catalyst account for 0.4% to 0.8% and 0.8% to 1.6% of the mass fraction of the monomer, respectively. For example, the mass fraction of the initiator to the monomer can be 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or any value within the above range, preferably 0.45%. For example, the mass fraction of the catalyst to the monomer can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6% or any value within the above range, preferably 1.25%. The role of the initiator is to guide free radical polymerization. If too little is added, the gel time is too long, which will cause the inhibition layer to be too thick. If too much is added, the gel time is too fast, and there is no time for subsequent test operations. The catalyst is mainly used to accelerate the process of free radical polymerization.
[0063] S15, casting: vacuum degassing the slurry after polymerization in S14 and pouring it into a mold to form a gel blank;
[0064] S16, demoulding and moisturizing: take out the gel blank, wash it, wrap it in plastic wrap and store it.
[0065] Specifically, the gel blank is taken out from the mold, and after the surface is cleaned, the blank is wrapped with a plastic wrap to prevent water evaporation.
[0066] In some embodiments of the present invention, in step S1, the preparation method of the sintering aid slurry is: mixing and ball milling the sintering aid powder and the polymer premix liquid.
[0067] It should be noted that the polymer premix used here is prepared in step S11.
[0068] S2, prepare the embedding powder raw materials: Pour silicon powder, silicon nitride powder, sintering aid and boron nitride powder into a ball mill, use alcohol as the ball milling medium to wet mix for 24-72 hours to obtain a slurry with uniform components, and place the obtained slurry in a constant temperature oven at 90°C for drying for 12 hours. Then, sieve the obtained powder through a 200-mesh screen to obtain a mixed powder with uniform particles.
[0069] The sintering aid powder is one or more of yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide, neodymium oxide, lutetium oxide and magnesium silicon nitride.
[0070] The mass ratio of the powder embedding raw material components is silicon nitride powder: sintering aid powder: boron nitride powder = x: (0.6-x): 0.4, (x = 0.1-0.5).
[0071] S3, debinding and sintering: removing organic matter in the porous silicon nitride ceramic precursor and then sintering to obtain the porous silicon nitride ceramic.
[0072] In some embodiments of the present invention, in step S3, removing organic matter from the porous silicon nitride ceramic precursor is specifically: heating to 400-800° C. in an air environment, keeping the temperature for 2-6 hours, and eliminating organic matter from the silicon nitride ceramic precursor;
[0073] Preferably, the temperature is raised to 500-700° C. in an air environment and kept at this temperature for 3-5 hours to eliminate organic matter in the silicon nitride ceramic precursor;
[0074] Preferably, the temperature is raised to 600° C. in an air environment and kept for 3 hours to eliminate organic matter in the silicon nitride ceramic precursor. Under this condition, the organic matter in the silicon nitride ceramic precursor can be completely discharged, avoiding the organic matter from volatilizing in a short time at high temperature during sintering, resulting in residual C inside, thereby reducing the structural performance.
[0075] In some embodiments of the present invention, in step S3, the sintering is gas pressure sintering, and the sintering temperature is 1600-1700°C, wherein the heating rate at 400-800°C is 0.5-2°C / min, the heating rate at 800-1200°C is 3-6°C / min, the heating rate at 1200-1700°C is 5-10°C / min, and the holding time is 1-2h.
[0076] Preferably, the sintering temperature is 1700°C, wherein the heating rate at 400-800°C is 2°C / min, the heating rate at 800-1200°C is 3°C / min, the heating rate at 1200-1700°C is 5°C / min, and the holding time is 2h.
[0077] Preferably, the sintering temperature is 1650°C, wherein the heating rate at 400-800°C is 2°C / min, the heating rate at 800-1200°C is 3°C / min, the heating rate at 1200-1700°C is 5°C / min, and the holding time is 2h.
[0078] Preferably, the sintering temperature is 1600° C., wherein the heating rate at 400-800° C. is 2° C. / min, the heating rate at 800-1200° C. is 3° C. / min, the heating rate at 1200-1700° C. is 5° C. / min, and the holding time is 2 h.
[0079] The above implementation is described in more detail below with reference to specific examples.
[0080] Example 1
[0081] This embodiment provides a method for manufacturing porous silicon nitride ceramics. Figure 1 As shown, the following steps are included:
[0082] S1. Silicon nitride ceramic green body with solid content of 45%.
[0083] S11. Ingredients: weigh 100 g of α-silicon nitride powder and 38.3 g of water.
[0084] S12. Prepare a premixed solution: dissolve monomer acrylamide (AM) and cross-linking agent N,N'-methylenebisacrylamide (MBAM) in water, and add 10% and 1% of the mass of water respectively; add dispersant ammonium polyacrylate (PAA-NH4) in an amount of 0.3% of the mass of the silicon nitride ceramic green body; add inhibitor catechol in an amount of 2% of the mass of the silicon nitride ceramic green body; add pH agent ammonia water (NH3·H2O) in an amount of 0.2% of the mass of the silicon nitride ceramic green body.
[0085] S13, prepare slurry: add the ingredients in S1 to the premixed liquid at a solid content of 45% and ball-mill to obtain a slurry, add initiator ammonium persulfate (APS) and catalyst N,N,N',N'-tetramethylethylenediamine (TEMED) to the slurry in succession, the added amounts being 0.45% and 1.25% of the monomer mass respectively, and obtain a silicon nitride ceramic blank with a solid content of 45% after gelation.
[0086] S2. Silicon powder, silicon nitride powder, sintering aid and boron nitride powder are prepared in a mass ratio of 1:3:3:3 and poured into a ball mill. Alcohol is used as a ball milling medium and wet mixed for 24 to 72 hours to obtain a slurry with uniform components. The obtained slurry is placed in a constant temperature oven at 90°C and dried for 12 hours. The obtained powder is then sieved through a 200-mesh sieve to obtain a mixed powder with uniform particles. Among them, the sintering aid is preferably one or more of yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide, neodymium oxide, lutetium oxide and magnesium silicon nitride.
[0087] S3, debinding and sintering: first place the silicon nitride ceramic green body in an air environment and heat it to 600°C, keep it warm for 3 hours to eliminate organic matter in the green body, then embed it into the prepared mixed powder and put it into a crucible, finally place it in a sintering furnace with nitrogen as protective gas, sinter it under the conditions of air pressure of 5MPa and sintering temperature of 1650°C, and keep it warm for 2 hours to obtain porous silicon nitride ceramics.
[0088] Example 2
[0089] Compared with Example 1, most of the steps are the same, except that the type and mass ratio of silicon nitride powder in step S1 is: α-type silicon nitride powder: β-type silicon nitride powder = 50:50;
[0090] Example 3
[0091] Compared with Example 1, most of the steps are the same, except that the type and mass ratio of silicon nitride powder in step S1 is: α-type silicon nitride powder:β-type silicon nitride powder=0:100.
[0092] Example 4
[0093] Compared with Example 1, most of the steps are the same, except that the mass ratio of silicon powder, silicon nitride powder, sintering aid and boron nitride powder in step S2 is 1:6:0:3.
[0094] Example 5
[0095] Compared with Example 1, most of them are the same, except that in step S2, the mass ratio of silicon powder, silicon nitride powder, sintering aid and boron nitride powder is 1:0:6:3.
[0096] Example 6
[0097] Compared with Example 1, most of them are the same, except that in step S2, the mass ratio of silicon powder, silicon nitride powder, sintering aid and boron nitride powder is 1:4.5:4.5:0.
[0098] Example 7
[0099] Compared with Example 1, most of the steps are the same, except that the mass ratio of silicon powder, silicon nitride powder, sintering aid and boron nitride powder in step S2 is 0:3.5:3.5:3.
[0100] Comparative Example 1
[0101] Compared with Example 1, most of the steps are the same, except that the mass ratio of silicon powder, silicon nitride powder, sintering aid and boron nitride powder in step S2 is 0:0:0:10.
[0102] Performance testing and characterization
[0103] 1) Mechanical properties, dielectric constant and average pore size test
[0104] The test methods and test instruments involved in the mechanical properties and dielectric constant tests are shown below: The complex dielectric constant is tested using the E8362B network analyzer (frequency: 8.2-12.4 GHz), and the porosity of the material is measured using the Archimede method. The results are shown in the table below.
[0105] sample Porosity / % Bonding strength / MPa Dielectric constant Average pore size / μm Example 1 53.7 128.2 2.9 1 Example 2 50.2 159.2 3.3 1.3 Example 3 54.0 76.5 2.5 0.8 Example 4 54.2 23.2 2.3 0.7 Example 5 53.2 33.2 2.9 0.6 Example 6 52.3 89.7 3.0 0.9 Example 7 53.4 78.3 2.9 0.8 Comparative Example 1 54.8 12.5 2.2 0.5
[0106] 2) XRD test:
[0107] See also Figure 2 As shown, a detailed study of Examples 1 to 7 and Comparative Example 1 revealed the presence of three typical XRD pattern characteristics, namely, SN-A type containing only α phase, SN-B type containing α and β phases, and SN-C type containing only β phase. Among them, Example 4, Example 5 and Comparative Example 1 are SN-A type containing only α phase, Example 1 and Example 2 are SN-C type containing only β phase, and Example 3, Example 6 and Example 7 are SN-B type containing α and β phases.
[0108] 3) SEM test
[0109] SEM was scanned and viewed using TESCAN's VEGA3 SUB device. Figures 3 to 5 It can be clearly seen that the SN-A type is entirely granular α-Si3N4, the SN-B type contains both granular α-Si3N4 and long columnar β-Si3N4, and the SN-C type contains only long columnar β-Si3N4, with crisscross grains inside and no residual impurities.
[0110] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A porous silicon nitride ceramic, characterized in that: The silicon nitride ceramic is formed by overlapping long rod-shaped grains, and the long rod-shaped grains are composed of β-Si3N4; The total porosity of the silicon nitride ceramic is 30% to 70%, the bending strength is 40 to 600 MPa, and the linear shrinkage is 0.2% to 1%.
2. The porous silicon nitride ceramic according to claim 1, characterized in that: The length of the crystal grains in the silicon nitride ceramic is 0.2-10 μm, the diameter is 0.1-2 μm, and the average aspect ratio is 5-15.
3. A method for preparing a porous silicon nitride ceramic according to any one of claims 1 to 2, characterized in that: The steps include: S1, gel injection molding silicon nitride ceramic green body; S2, mixing silicon powder, silicon nitride powder, sintering aid and boron nitride powder to obtain a buried powder raw material; S3, removing organic matter from the ceramic green body, and embedding the obtained green body with embedding powder raw materials, and obtaining porous silicon nitride ceramics after sintering.
4. The porous silicon nitride ceramic according to claim 3, characterized in that: The preparation method of the silicon nitride ceramic green body is as follows: S11, uniformly mixing the monomer, cross-linking agent, polymerization inhibitor, pH agent, dispersant and water to obtain a polymer premix solution; S12, selecting silicon nitride powder as the ceramic powder; S13, mixing the polymer premix and the ceramic powder evenly, and dispersing them by ball milling to obtain a ceramic slurry; S14, adding an initiator and a catalyst to the ceramic slurry, pouring it into a mold for molding, and obtaining a silicon nitride ceramic green body.
5. The method for preparing a porous silicon nitride ceramic according to claim 4, characterized in that: In S12, the silicon nitride powder satisfies at least one of the following conditions: ① The silicon nitride powder is composed of α-type silicon nitride powder and β-type silicon nitride powder, and the ratio of the two is (0-100):(100-0); ② The median particle size of the silicon nitride powder is 0.5 to 10 μm.
6. The method for preparing a porous silicon nitride ceramic according to claim 4, characterized in that: In S13, the solid phase volume content of the ceramic slurry is 15% to 65%, and the high molecular polymer content is 1% to 10% of the total mass of the ceramic slurry.
7. The method for preparing a porous silicon nitride ceramic according to claim 3, characterized in that: In S2, the mixed powder is prepared specifically as follows: silicon powder, silicon nitride powder, sintering aid and boron nitride powder are poured into a ball mill, wet-mixed for at least 48 hours using alcohol as a ball milling medium to obtain a slurry with uniform components, the slurry is placed in a constant temperature oven at a maximum of 90° C. and dried for at least 12 hours, and sieved to obtain a mixed powder.
8. The method for preparing a porous silicon nitride ceramic according to claim 3, characterized in that: In S2, the sintering aid powder is one or more of yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide, neodymium oxide, lutetium oxide and magnesium silicon nitride.
9. The method for preparing a porous silicon nitride ceramic according to claim 3, characterized in that: In S2, the mass ratio of silicon nitride powder, sintering aid powder and boron nitride powder in the powder embedding raw material is (0.1-0.5):(0.5-0.1):(0.4).
10. The method for preparing a porous silicon nitride ceramic according to claim 3, characterized in that: In S3, the organic matter in the porous silicon nitride ceramic precursor is removed by: heating to 400-800°C in an air environment, keeping the temperature for 2-6 hours, and eliminating the organic matter in the ceramic blank; pouring the powder embedding raw material into a sintering crucible, which occupies 50%-70% of the volume of the crucible, and then embedding the ceramic blank into the powder in the crucible; The sintering is gas pressure sintering, and the sintering temperature is 1600-1700°C, wherein the heating rate at 400-800°C is 0.5-2°C / min, the heating rate at 800-1200°C is 3-6°C / min, the heating rate at 1200-1700°C is 5-10°C / min, and the holding time is 1-2h.
Citation Information
Patent Citations
Preparation method of high performance large size silicon nitride ceramic material
CN106518089A
Silicon nitride porous ceramics material rapid curing molding preparation method
CN107352781A
Preparation method for silicon nitride whisker and silicon nitride nanowire enhanced silicon nitride base wave-transparent ceramics
CN109320276A
Method for preparing porous silicon nitride ceramic by using ultralow-content sintering aid
CN111196729A
Method for preparing high-toughness high-temperature-resistant directionally-arranged silicon nitride monolithic porous ceramic
CN114804912A